Perioperative changes in plasma cardiac troponin I concentration during mitral valvuloplasty for severe mitral regurgitation in dogs - Takeki Ando; Kippei Mihara; Isamu Kanemoto; Hideo Akiyoshi (Open Veterinary Journal, 2024)
Background: Mitral valvuloplasty (MVP) is a surgical procedure for treating severe mitral regurgitation in dogs. Although MVP is considered highly invasive, the extent of myocardial injury, postoperative complications, and recovery has not been evaluated. Aim: This study examined the degree of MVP invasiveness, the extent of myocardial damage, postoperative complications, cardiomyocyte recovery, and timing of hospital discharge. Methods: Cardiac troponin I (cTnI) was used to investigate the myocardial damage caused by cardiac arrest associated with a surgical approach to the myocardium in 13 patients with MVP and 5 controls with patent ductus arteriosus who underwent similar anesthesia and thoracotomy. Results: The level of cTnI peaked 1 day after surgery and was significantly higher in the MVP group (median, 19.90 ng/mL) than in control group (median, 1.50 ng/mL P < 0.001). At day 7, the cTnI level was significantly higher in the MVP group (1.9 ng/mL) than in control group (0.1 ng/mL) (P < 0.001), and recovery to the preoperative level took 10 days in the MVP group but returned to the preoperative level at day 7 in control group. Although the mean arterial pressure of cardiopulmonary bypass at the time of use was 42.92 mmHg, the peak cTnI levels in the two patients who exhibited a temporary decrease of 20 mmHg or less (46.03 ng/mL) were significantly higher than in the other 11 patients (19.70 ng/mL) (P < 0.05). Preoperative cTnI levels were correlated with the severity of postoperative complications (P = 0.03, F = 0.71). Conclusion: The results showed that MVP caused temporary greater myocardial tissue damage than thoracotomy, but postoperative recovery was smoother. A high preoperative cTnI level requires relatively more careful postoperative management, and measuring the level of cTnI over time after surgery can provide information about the extent of myocardial damage and recovery from surgery and help determine the time of discharge. [Open Vet J 2024; 14(7.000): 1625-1633]